Genito urinary fistula: a series of 1704 cases - Nawaz, Haq (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To review our experience in causes, diagnosis and basic principles of surgical treatment of urogenital fistulas. Methods: A retrospective study of 1704 patients with different types of urogenital fistulas were reviewed between October 1995 to October 2018. They were analyzed with regard to age, parity, casual factor, mode of treatment and outcome. Patients were also evaluated at two or three weeks initially, three monthly and later depending upon symptoms. Results: We reviewed our series of female urogenital fistulas that have been treated over a 22 years period. Out of these 1704 cases 864 (62.44%) were Vesico vaginal fistulas, 432 (25.35%) were Urethro vaginal fistulas and 188 (12.2%) were Uretero vaginal. Majority of the patients were young in child bearing age between 16 and 30 years of age, although age range was wide i.e., 11 to 50 years. The most common cause of urogenital fistulas were Obstetrical trauma due to obstructed labor in 400(37.59%) & Gynecological (hysterectomy 180(18.79%) & caesarian section in 72 (6.77%). Patients of Uretero vaginal fistulas were mainly due to unrecognized ureteral injuries during Gynecological procedures (hysterectomy in 136 cases & caesarian section in 10 cases. For repair of vesico vaginal fistulas Transvaginal route for repair was used in 424(39.84%) patients, while Thans abdominal route for repair was used in 560 (52.63%) patients. There were 32 (12.03%) failures in Vesico vaginal fistulas with a success rate of 88%. Mean Hospital stay was 15+ 3.5 days (range 4-30 days) and a mean follow-up of 8+ 3.2 months (range 4 months to 2 years). Conclusions: Management of Urogenital fistulas are among the most distressing complications of obstetric and gynecologic procedures. The patients suffer physically, emotionally and socially. The lack of skilled supervision and adequate obstetric emergency facilities are to blame.